A matinta tem a cor da chuva: ludicidade como estratégia de ensino-aprendizagem para Educação ambiental - DIAS, Maírna Costa (Universidade Federal do Pará, 2017)
Whereas popular culture was established as a colorful mosaic of myths, rituals, values and knowledge, and they, in turn, are often absent from school spaces impeding the formation of critical social subjects and able to appreciate the local culture we recognize in the Amazonian legends (represented in this work by the legend of Matinta Perera) potential rescue tools, recovery and reinterpretation of the Amazon culture. The objective of this research was to try to understand the possibilities and approaches between Amazon mythopoeic and environmental education attentive and contextualized to the rich imagery of popular culture present in children's speech. We develop our study in Early Childhood Education School "Ecoescola Rita Nery" located in Tenoné District, Bethlehem, PA to the following methodology: focus group training with teachers of Ecoescola for discussion and planning of activity, thematic delimitation "urban waste and Matinta Perera "story staging tied the chosen theme," retelling "of the story by children and collection of narratives. We note, by the children's narratives, the character Matinta Perera presented with diverse character which provided an opportunity for children to incorporate habits and attitudes "ecologically correct", started to behave as environmental multipliers.